Improving leaping ability in elite rhythmic gymnasts - Hutchinson, M. R.; Tremain, L.; Christiansen, J.; Beitzel, J. (Medicine & Science in Sports & Exercise, 1998)
Purpose: The purpose of this study was to improve the leaping ability of athletes in rhythmic gymnastics, a high leap demanding sport, using a controlled course of jump training.